Ab initio calculations of mechanical properties of bcc W–Re–Os random alloys: effects of transmutation of W. (3rd June 2016) - Li, Xiaojie; Schönecker, Stephan; Li, Ruihuan; Li, Xiaoqing; Wang, Yuanyuan; Zhao, Jijun; Johansson, Börje; Vitos, Levente
Abstract: To examine the effect of neutron transmutation on tungsten as the first wall material of fusion reactors, the elastic properties of W1− x − y Re x Os y (0 ⩽ x, y ⩽ 6%) random alloys in body centered cubic (bcc) structure are investigated systematically using the all-electron exact muffin-tin orbitals (EMTO) method in combination with the coherent-potential approximation (CPA). The calculated lattice constant and elastic properties of pure W are consistent with available experiments. Both Os and Re additions reduce the lattice constant and increase the bulk modulus of W, with Os having the stronger effect. The polycrystalline shear modulus, Young's modulus and the Debye temperature increase (decrease) with the addition of Re (Os). Except for C 11, the other elastic parameters including C 12, C 44, Cauchy pressure, Poisson ratio, B / G, increase as a function of Re and Os concentration. The variations of the latter three parameters and the trend in the ratio of cleavage energy to shear modulus for the most dominant slip system indicate that the ductility of the alloy enhances with increasing Re and Os content. The calculated elastic anisotropy of bcc W slightly increases with the concentration of both alloying elements. The estimated melting temperatures of the W–Re–Os alloy suggest that Re or Os addition will reduce the melting temperature of pure W solid. The classical Labusch–Nabarro model for solid-solution hardening predicts larger strengthening effects in W1− y Os y than in W1− x Re x . A strong correlation between C ′ and the fcc–bcc structural energy difference for W1− x − y Re x Os y is revealed demonstrating that canonical band structure dictates the alloying effect on C ′. The structural energy difference is exploited to estimate the alloying effect on the ideal tensile strength in the [0 0 1] direction.